Global Procument - An Advantage Or A Disaster To Malaysian Industries - Tai, Chew Theng (2006)
The findings of the study are useful in providing an overview on global procument for Malaysian managers in the Malaysian context. The findings of the study also indicate that even though there are several obstacles in dealing with global procuments, majority of the organizations do agree that global procurement has improved organizations' performance.